PERSPECTIVE OF IN VITRO LYMPHOCYTES ANTIGENICITY EVALUATION FOR THE DIAGNOSTICS OF ACUTE BRUCELLOSIS - M. V. Kostyuchenko (Sankt-Peterburg : NIIÈM imeni Pastera, 2017)
The brucellosis remains to one of the most urgent dangerous infections in regions with developed livestock production. An exclusive polymorphism of symptoms, variety of forms of a disease, small informational content of results of routine laboratory all-clinical inspection, quite often leads to diagnostic mistakes at a pre-hospital stage. Improvement of a complex of laboratory diagnosis of a brucellous infection demands development of the modern padding methods of verification based on cell-like factors of immunity as leaders in an immunogenesis and a pathogenesis of a brucellosis. Considering the leading role of cell-like immunity in formation of protection against the majority of bacteriemic especially dangerous infections, studying of cell-like reaction in response to antigenic stimulation, it is necessary to consider the most informative (marker) and objective at assessment of immunologic reorganization of an organism at a disease or vaccination. The following markers (receptors) of activation of lymphocytes can act as perspective indexes of a specific cell-like antigenreactivity: CD25 — a high-affine receptor of interleukin 2 (IL-2Ra), a marker of early activation of Tlymphocytes; HLA-DR — an antigen of the main complex of a histocompatibility of a class II, an expression of a marker is associated not only with late, but also long-lived activation of lymphocytes; CD95 (Fas, APO-1) — a receptor of an induction of an apoptosis (“cell death”), a marker of “late” activation (CD4+ lymphocytes is presented mainly) and Fas L (CD178) — a receptor of an induction of an apoptosis, expresses generally on CD8+ cages. The work purpose — to estimate an opportunity and prospects of use of technology of a flowing cytofluorometry and the in vitro cell tests for diagnosis of a acute brucellosis. 35 people with the diagnosis “Acute brucellosis” and 12 people — not the patients who did not have a brucellosis, are not vaccinated against a brucellosis (control group) participated in a research. Blue blood served as material of a research. Defined quantity of the lymphocytes expressing receptors of CD25, HLA-DR, CD95, CD95L (CD178) at activation by a specific antigen. The received results processed statistically with use of Microsoft Excel 2010. During the research it is established that intensity an antigen-stimulated activation of lymphocytes of in vitro, it is possible to use as a marker of a acute brucellous infection at the person. The most perspective indexes of activation of lymphocytes of in vitro, it is possible to consider receptors to IL-2 (CD25) and apoptosis markers — CD95, CD95L (CD178). Thus, the conducted researches indicate an opportunity and the actual prospect of use of technology of a flowing cytofluorometry and cell-like in vitro tests for diagnostics of a acute brucellosis.